Strengthening Emergency Department Performance through Multidisciplinary Teamwork: A Systematic Review - Alshehri, Amira Abdullah Qalit; Alqahtani, Mohammed Hamed; Alasmari, Khalid Ahmed Khazim; Muidh, Abdullah Mani Jaber; Alabatheen, Rasheed Salem Mohd; Alyami, Sami Nasser Misfer; Alamri, Faisal Muthyib Awad Allah; Aljoha, Omar Raja Eaysh; AlRashidi, Sami Suwailem Saeed; Aljohani, Yousef Mohammed Furayj (Journal of Posthumanism, 2024)
Emergency departments (EDs) are the frontline of healthcare systems, often faced with high patient volumes, critical time pressures, and increasingly complex cases. To address these challenges, multidisciplinary teamwork has emerged as a vital strategy to enhance patient care, safety, and overall departmental efficiency. This systematic review explores the role of multidisciplinary health teams—including physicians, nurses, paramedics, pharmacists, social workers, and allied health professionals—in strengthening ED performance. Following PRISMA guidelines, peer-reviewed literature published between 2010 and 2025 was analyzed to examine the impact of team-based collaboration on patient outcomes, quality of care, and operational efficiency. Evidence indicates that multidisciplinary approaches significantly reduce medical errors, improve triage accuracy, shorten patient waiting times, and enhance satisfaction for both patients and healthcare providers. However, barriers such as communication breakdowns, hierarchical structures, and resource limitations persist, potentially hindering effective collaboration. The review highlights strategies including interprofessional training, leadership support, standardized care pathways, and digital health integration as enablers of stronger team-based care in EDs. Ultimately, the findings underscore that effective multidisciplinary teamwork is not only essential for optimizing patient outcomes in emergency settings but also for sustaining healthcare system resilience and preparedness.